Analysis of the Reliability of Security Check Point Equipment in Inspecting Passenger Luggage at Juanda International Airport, Surabaya - Rifqi Lucky Anggoro; Walid Jumlad (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
In accordance with SKEP/2765/XII/2010 regulations, all those who will enter the airport area must first be checked through the Security Check Point. The problem is with the equipment used to check passenger goods through the Security Check Point. Work equipment with adequate conditions in a condition suitable for use and properly maintained can make it easier for the operation process to run smoothly so that items that are prohibited or not allowed to enter the aircraft cabin are prevented from escaping. The research uses a qualitative descriptive method, which is arranged systematically from interviews, observation and documentation. Qualitative research is research that is applied to conduct investigations, make discoveries, describe and explain the quality of influence without being able to give a description, measure or describe using a quantitative approach. Based on the results of the interviews and observations, it can be explained that the Security Check Point equipment must be checked regularly and recorded starting from the Aviation Security officer's report to the Airport Electronics technician officer. 4 X-ray equipment only 1 X-ray has problems so the inspection process is sometimes closed, 4 WalkTrough Metal Detector equipment is safely under control for inspection. In some HandHeld Metal Detector tools, problems often occur, the HandHeld Metal Detector report is not attached because if the sensor from the HandHeld Metal Detector equipment experiences problems, the equipment is immediately replaced with a new one.